Three-dimensional soft tissue analysis of the hand: a novel method to investigate effects of acromegaly - Hoevenaren, Inge A.; Wagenmakers, M. A. E. M.; Roerink, S. H. P. P.; Netea-Maier, R. T.; Ulrich, D. J. O.; Maal, Thomas J. J. (European journal of plastic surgery, 2016)
Background Acral overgrowth is a highly common clinical sign in patients with active acromegaly. To what extent this overgrowth persists after long-term remission of acromegaly is largely unknown. Using the new imaging technique of three-dimensional (3D) stereophotogrammetry, it is possible to accurately investigate soft tissue changes of the hand. The aim of the recent study was to compare the 3D soft tissue characteristics of the hands of patients in long-term remission of acromegaly to those of a healthy pair matched control group. Methods A case-control study was performed at a tertiary referral center. Twelve patients in remission of acromegaly (58 % male, mean age 58.3 years, mean BMI 29.6 kg/m 2 ) were compared to twelve age-, gender-, ethnicity-, and BMI-matched control subjects. Of each individual, 3D photographs of both hands were acquired and analyzed using a 3D computer software program. Results The patients in long-term remission of acromegaly have overgrowth of soft tissue of the hand compared to matched control subjects, with a larger length and width of the hand ( p = 0.0025, p = 0.0017, respectively). Furthermore, the diameters measured at the proximal interphalangeal (PIP) joints of the individual fingers are larger in the acromegaly patients. Conclusions Significant soft tissue overgrowth of the hand persists in former acromegaly patients, even after long-term remission. Analysis of 3D hand photographs is an accurate and easy tool to evaluate the acral soft tissue patterns in acromegaly. Level of Evidence: Level III, diagnostic study.